Therapeutic Impact of Human Serum Albumin–Thioredoxin Fusion Protein on Influenza Virus-Induced Lung Injury Mice - Tanaka, Ryota; Ishima, Yu; Enoki, Yuki; Kimachi, Kazuhiko; Shirai, Tatsuya; Watanabe, Hiroshi; Chuang, Victor T. G.; Maruyama, Toru; Otagiri, Masaki (Frontiers in Immunology, 2014)
Reactive oxygen species (ROS) are the primary pathogenic molecules produced in viral lung infections. We previously reported on the use of a recombinant human serum albumin (HSA)-thioredoxin 1 (Trx) fusion protein (HSA-Trx) for extending the half-life Trx, an endogenous protein with antioxidant properties. As a result, it was possible to overcome the unfavorable pharmacokinetic and short pharmacological properties of Trx. We hypothesized that HSA-Trx would attenuate the enhanced ROS production of species such as hydroxyl radicals by neutrophils during an influenza viral infection. The levels of 8-hydroxy-2’-deoxyguanosine and 3-nitrotyrosine were used as indices of the antioxidant activity of HSA-Trx. In addition, the cytoprotective effects of HSA-Trx were examined in PR8 (H1N1) influenza virus-induced lung injured mice. The findings show that HSA-Trx reduced the number of total cells, neutrophils and total protein in BALF of influenza virus-induced lung injured mice. The HSA-Trx treatment significantly decreased the level of 8-hydroxy-2’-deoxyguanosine and 3-nitrotyrosine, but failed to inhibit iNOS expression, in the lungs of the virus-infected mice. On the other hand, Tamiflu® treatment also significantly suppressed the production of inflammatory cells and neutrophil infiltration, as well as the protein level in BALF and lung histopathological alterations caused by the influenza virus. The suppressive effect of Tamiflu® was slightly stronger than that of HSA-Trx. Interestingly, Tamiflu® significantly decreased virus proliferation, while HSA-Trx had no effect. These results indicate that HSA-Trx may be of therapeutic value for the treatment of various acute inflammatory disorders such as influenza-virus-induced pneumonia, by inhibiting inflammatory-cell responses and suppressing the overproduction of NO in the lung.